Respuesta :
Answer:
-5
Step-by-step explanation:
Using rules of exponents we can change this equation to
y ^ (-9 * b) = y^45
-9*b = 45
b = -5
Answer:
The correct answer is - 5
Step-by-step explanation:
![Ver imagen 0JakeFromStateFarm0](https://us-static.z-dn.net/files/d9d/40e96f7a71852da999b252bbb58d26d7.jpeg)
Answer:
-5
Step-by-step explanation:
Using rules of exponents we can change this equation to
y ^ (-9 * b) = y^45
-9*b = 45
b = -5
Answer:
The correct answer is - 5
Step-by-step explanation: